Pattern of Stroke and Short Term Outcome of COVID-19 Patients admitted in a Dedicated Stroke Unit at Referral Neurology Hospital of Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: COVID-19 was declared as a pandemic by WHO on March 11, 2020. Though the most common and important presentation is with respiratory disease, reports of neurological features are increasing.Objective: In this study it was described the pattern of stroke in COVID-19 patients admitted in a dedicated stroke unit and their short term outcome.Methodology: This single arm, single centreprospective cohortstudy was conducted in the Stroke Unit of National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from April to August, 2020 and wasincluded acute stroke patients irrespective of age and sex who were found RT-PCR positive for SARS CoV-2. The patientswere evaluated clinically, biochemically and by imaging. After diagnosis patients were referred to a COVIDdedicated hospital and were followed up over phone for 4 weeks from the day of admission in stroke unit to assess short term outcome.Results: Among the 41 patients, 21 were male and 20 female with an age range of 26 to 90 years where 58.5% patients were aged 60 and above. Majority (58.5%) of them came from different urban areas. Common co-morbidities were Hypertension (68.3%) and Diabetes mellitus (39%). Most common presenting features were hemiplegia (48.8%) and altered level of consciousness (39%). More than seventy percent (70.7%) patients had GCS of 10 or less and 56.1% patients had oxygen saturation 90% or less in room air. CT brain imaging revealed infarct in 39% and hemorrhage in 51.2%. Chest radiography revealed abnormality in 14.6% cases. Regarding the short term outcome, total 20 (48.8%) patients died where 7 died before referral to COVID-19 dedicated hospital. Death was higher in hemorrhagic stroke but there was no significant association between outcome and the type of stroke (p value>0.05).Conclusions: Hemorrhagic stroke is the most commonly occurring stroke among the COVID-19 patients and associated with p oor outcome.Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 25-28